Badan Usaha Milik Desa (Bumdes) Di Kabupaten Banyumas: Model Pergeseran Paradigma Pengelolaan Potensi Desa - Sutikno, Chamid; Atika, Zaula Rizqi; Wijaya, Shadu Satwika; Mujib, Mujib (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2022)
AbstrackThe formation of BUMDes has been in accordance with the direction of the development of the paradigm of public administration, because there has been a paradigm shift from Old Public Administration to New Public Management which is implemented in the village government. Therefore, the establishment of Village Owned Enterprises (BUMDes) is one model of utilizing village financial capacity to utilize village potential and assets. The purpose of this study is to compare the traditional management of village potential through the village government and management based on public enterprises (public enterprise). The results of the study indicate that there are fundamental differences in the management of village potential. Therefore, the shift in the village potential management model from the government to a public enterprise for managing village potential has been on the right path. BUMDes as a form of public enterprise at the village level is moving from a bureaucratic paradigm to the business sector, but not just pure business but social business.  Keywords: Local Competitiveness, New Public Management, Public Enterprise, Social Businesses Model. AbstrakPembentukan BUMDes telah sesuai dengan arah perkembangan paradigma administrasi publik, karena terjadi pergeseran paradigma dari Old Public Administration ke New Publik Management yang diterapkan di pemerintah desa. Oleh karena itu, pembentukan Badan Usaha Milik Desa (BUMDes) merupakan salah satu model pemanfaatan kapasitas finansial desa untuk pemanfaatan potensi dan aset desa. Tujuan penelitian ini membandingkan pengelolaan potensi desa secara tradisional melalui pemerintah desa dan pengelolaan berbasis badan usaha publik (public enterprice). Hasil penelitian menunjukkan bahwa terdapat perbedaan mendasar dalam pengelolaan potensi desa. Oleh karena itu, pergeseran model pengelolaan potensi desa dari pemerintah ke arah public enterprise untuk pengelolaan potensi desa telah berada di jalan yang benar. BUMDes sebagai bentuk public enterprise di level desa bergerak dari paradigma birokratik ke sektor bisnis, namun bukan sekadar bisnis murni melainkan bisnis sosial.  Kata Kunci: Local Competitiveness, New Public Management, Public Enterprice, Social Businesses Model.